Karakteristik Selai Lembaran Dari Campuran Kolang-kaling (Arenga pinnata, M) dan Buah Terung Belanda (Solanum betaceum) - Devi Silsia; Indah Yulastri; Marniza Marniza; Ulfah Anis (Jurnal Teknologi Agro-Industri, 2022)
This study aims to determine the effect of the comparison between kolang kaling and dutch eggplant on the physical, chemical and organoleptic characteristics of sheet jam. This study used a completely randomized design (CRD) of one factor with 5 treatments and 3 repetitions. The research use Analysis of Variants (ANOVA), then continued with Duncan 's New Multiple Range (DNMRT) at the level of 5%. The treatment used is a mixture of kolang-kaling and dutch eggplant namely A (100%: 0%), B (90%: 10%), C (80%: 20%), D (70%: 30%) and E ( 60%: 40%). The results showed that the mixture of kaling and eggplant gave a significant different effect on water content, pH value, vitamin C, total dissolved solids and crude fiber, and gave no significant effect on the fold test. The results showed the treatment of sheet jam from a mixture of kolang-kaling and dutch eggplant Netherlands at a concentration of 70%: 30% (treatment D) is a sheet jam product which is the most preferred with a moisture content of 29.89%, 5/10 color (10R), fold test (4.00), pH 3.63, vitamin C 6.16 mg, total dissolved solids 64.23 0Brix and crude fiber 1.03% and organoleptic acceptability with color values ​​3.84, aroma 3.24, texture 3 , 76 and taste 4.00.